2018
DOI: 10.1590/s1980-220x2017024203308
|View full text |Cite
|
Sign up to set email alerts
|

Incidência de quedas e ações preventivas em um Hospital Universitário

Abstract: Objective Describing the incidence of falls and its relation with preventive actions developed in a Brazilian university hospital. Method A retrospective longitudinal study. Hospitalized adult patients in the clinical, surgical, psychiatric and emergency units who suffered a fall in the institution, and who had the event notified in the period from January 2011 to December 2015 were included in the study. The data were collected from the institution's management information system and analyzed in the SPSS stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 17 publications
(24 reference statements)
0
10
0
12
Order By: Relevance
“…In the present study, 43% of the total number of events were damaged, being mostly mild (80%), followed by severe (11.9%) and moderate (7.3%). The rate of damage due to falls found in other investigations carried out in the context of hospital admission was 26 to 38.6% (5)(6)8,(13)(14)17) .…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In the present study, 43% of the total number of events were damaged, being mostly mild (80%), followed by severe (11.9%) and moderate (7.3%). The rate of damage due to falls found in other investigations carried out in the context of hospital admission was 26 to 38.6% (5)(6)8,(13)(14)17) .…”
Section: Discussionmentioning
confidence: 68%
“…The falls do not occur uniformly in the hospital environment and depend on the patient profile, the characteristics of the unit, the processes and practices adopted, being more prevalent in units with greater numbers of elderly people, in specific areas such as neurology and rehabilitation, or in those with lower nursing personnel size (8,(18)(19) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The care provided and their efforts in this regard must ensure the safety and well-being of the elderly (20) . The safety of the environment must be guaranteed for all patients, regardless of risk, since hospitals represent an unknown and unfamiliar environment, and are more critical for the elderly (23) . Policies and (legislation) must allow the detection of poor practices and deal with situations where safety may be compromised (20) .…”
Section: Introductionmentioning
confidence: 99%
“…It was found that lower incidence of falls resulted from the implementation of preventive measures, suggesting that the prevention protocol, the use of a risk assessment scale, the systematic raising of awareness and guidance to patients, family members and the nursing staff may have impacted the occurrence of the event in the institution. 31 It should be emphasized that all measures to prevent medication errors and falls are relevant. However, what this review adds is that due to the association of these types of incidents with the dimensions of Burnout, it is also necessary to improve the health of the workers, especially in relation to emotional exhaustion and depersonalization.…”
Section: Main Objective/type Of Studymentioning
confidence: 99%